Comparison of the Murchison CM2 and Allende CV3 chondrites. (9th February 2021) - Fendrich, Kim V.; Ebel, Denton S.
Abstract: The size distribution, abundance, and physical and chemical characteristics of chondritic inclusions are key features that define the chondrite groups. We present statistics on the size and abundance of the macroscopic components (inclusions) in the Murchison (CM2) and Allende (CV3) chondrites and measure their general chemical trends using established X‐ray mapping techniques. This study provides a fine‐scale assessment of the two meteorites and a semiquantitative evaluation of the relative abundances of elements and their distribution among meteorite components. Murchison contains 72% matrix and 28% inclusions; Allende contains 57% and 43%, respectively. A broad range of inclusion sizes and relative abundances has been reported for these meteorites, which demonstrates the necessity for a more standardized approach to measuring these characteristics. Nonetheless, the characteristic mean sizes of inclusions in Allende are consistently larger than those in Murchison. We draw two significant conclusions (1) these two meteorites sampled distinct populations of chondrules and refractory inclusions, and (2) complementary Mg/Si ratios between chondrules and matrix are observed in both Murchison and Allende. Both support the idea that chondrules and matrix within each chondrite group originated in single reservoirs of precursors with approximately solar Mg/Si ratios, providing a constraint on astrophysical models of the origin of chondrite parent bodies.